Comparison of Respiratory Pathogen Detections from Routine Hospital Testing and Expanded Systematic Testing from the Minnesota Severe Acute Respiratory Illness Surveillance Program, 2015–2016. (4th October 2017) - Steffens, Andrea; Friedlander, Hannah; Como-Sabetti, Kathryn; Boxrud, Dave; Bistodeau, Sarah; Strain, Anna; Reed, Carrie; Lynfield, Ruth; Fowlkes, Ashley
Abstract: Background: Hospital testing for respiratory pathogens is nonsystematic, leading to potential missed detection of clinically relevant pathogens. The Minnesota Severe Acute Respiratory Illness (SARI) surveillance program monitors hospitalizations due to acute respiratory illness and conducts systematic testing for several respiratory pathogens. We assessed viruses detected by the hospital and additional detections identified by expanded testing. Methods: Residual upper respiratory specimens collected from patients hospitalized for suspected respiratory illness for routine diagnostic testing at three hospitals, including one children's hospital, were submitted to the Minnesota Department of Health (MDH). Specimens were tested for 18 respiratory viruses by RT-PCR. Clinical and hospital test data were collected through medical record review. Results: From September 2015 to August 2016, 2, 351 hospitalized SARI patients were reported, with the following age distribution: 57% <5 years, 13% 5–17 years, 30% ≥18 years. Among all SARI patients, 97% (2, 273) had hospital-based, clinician-directed testing for viral pathogens. Viruses were detected among 47% (1, 077) of tested patients, among which testing methods included PCR (85%), rapid antigen (13%), and culture (2%); 74% were tested on the day of admission. Most common viruses detected by clinical testing included respiratory syncytial virus (41%), rhinovirus/enterovirus (31%), and influenza (15%) (Figure 1). Systematic RT–PCR testing at MDH identified 1, 600 (68%) patients positive for ≥1 respiratory virus, identifying previously unknown detections among 35% (820) of SARI patients (Figure 2). Of 1, 272 patients with no virus identified at the hospital, 46% (586) had a viral detection at MDH. Patients aged <18 years were significantly more likely to have an additional pathogen detected by MDH testing than those aged ≥18 years ( P  < 0.01), including rhinovirus/enterovirus, adenovirus, human metapneumovirus, and coronaviruses. Conclusion: Systematic, expanded testing at MDH identified a higher proportion of respiratory pathogens among SARI patients compared with clinical laboratory testing. Additional testing for clinically relevant respiratory pathogens may inform medical decision-making. Disclosures: All authors: No reported disclosures.